An adaptive D-STATCOM control scheme utilising impedance estimation - Rose, Christopher James (2016)
Concerns for energy security and the environment are driving significant changes in the way electrical power is generated and distributed. In many parts of the world, electrical power systems are gradually changing from centralised systems with a small number of large generators and substations performing most control operations to distributed systems, with a large number of devices providing control at a local level. Power electronic converters have an increasingly important role to play in modern electrical power systems. One example of power electronics in such systems is the STATCOM, a power electronic device which can be used to provide an efficient and effective means of controlling power system voltages. This thesis presents an investigation into STATCOM voltage control for distribution level power networks.